PENGARUH DISIPLIN KERJA DAN KEMAMPUAN KERJA TERHADAP KINERJA PNS DINSOS PAPUA BARAT - Sylvia Margareth Sabarofek; Paulus Habel Sawor; Makarius Bajari (Cakrawala Management Business Journal, 2020)
The purpose of this study was to study the effect of work discipline variable and simultaneous work ability and competence at the West Papua Province Social Service Office. This research is a quantitative study. The sampling method uses Non Probability Sampling and the sampling technique uses Saturated Sampling. The result of this study indicate that the variable work discipline is not significant on employee performance, and subsequent research result indicate that work ability variables partially have a siginificant effect on employee performance. Also showed a variable work discipline and work ability significantly to the performance of employess in the West Papua Province Social Service Office. Improving the performance of West papua Provincial Social Service Office employees must provide work coordination and work capabilities together to improve employee performance.